1975
DOI: 10.1111/j.1399-3054.1975.tb01852.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Endogenous Plant Hormones in Cherry Tomato Fruits during Development and Maturation

Abstract: Hormonal extracts of cherry tomato fruits (Lycopersicon esculentum Mill.) cv. Small Fry at different stages of fruit development and maturation were bioassayed for their auxin, gibberellin, cytokinin and growth inhibitor activities. In general, the levels of endogenous growth promoters were much higher in the young developing fruits than in the more mature fruits. Free cytokinin levels were highest in the first two weeks of development then declined rapidly. However, cytokinin activity in the ribotide fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0
1

Year Published

1977
1977
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 15 publications
1
28
0
1
Order By: Relevance
“…IAA [4] and cytokinin i .e . isopentenyl adenine, isopentenyl adenosine, zeatin and zeatin riboside [2,28] . Apparently, there is less cell division as well as less cytokinin and diffusible auxin in GA-induced fruits than in seeded fruits [5], but cell division in the GA-fruits can be stimulated if 4-CPA is applied within 3 days of the GA induction [8] .…”
Section: Fruit Set and Fruit Growth Potentialmentioning
confidence: 99%
“…IAA [4] and cytokinin i .e . isopentenyl adenine, isopentenyl adenosine, zeatin and zeatin riboside [2,28] . Apparently, there is less cell division as well as less cytokinin and diffusible auxin in GA-induced fruits than in seeded fruits [5], but cell division in the GA-fruits can be stimulated if 4-CPA is applied within 3 days of the GA induction [8] .…”
Section: Fruit Set and Fruit Growth Potentialmentioning
confidence: 99%
“…b. To determine the following organic substances, ethanolic extraction of pods was prepared as described by Abdel-Rahman et al (1975). Free phenolics concentration was determined by a modified FolinCiocalteu method at 650 nm according to William et al (1965).…”
Section: Determination Of Organic Compoundsmentioning
confidence: 99%
“…The bioassay systems, other than tissue culture, are relatively rapid methods but poor in specificity compared to tissue culture. Recently a convenient bioassay with Amaranthus seedli ngs6) has been used to survey the changes in the endogenous cytokinin levels in cherry tomato fruits 7 ) and to clarify cytokinins in cones of hop plant. S ) During the course of searching for cell division regulators from persimmon fruits, we isolated methyl pheophorbides a and b as callus growth inhibitors.9) In the present investigations, we found that the methanol extract of the fruits of Diospyrous kaki inhibited remarkably the cytokinin-induced betacyanin synthesis in the seedlings of Amaranthus caudalus.…”
mentioning
confidence: 99%
“…Elephantopin and vernolepin, which contain a-methylene-r-Iactone function in the molecule, were reported to inhibit not only growth of cells derived from human carcinoma of the nasopharynx (KB)l5) but also extension growth of wheat coleoptile sections. 16 ) Cysteine adducts of these cytotoxic lactones showed lower inhibitory activities against KB cell cultures/ 7 ) indicating that the cytotoxicity of a-methylener-lactones may result from alkylation of nucleophilic centers in a biological system. Sakai et al 18 ) reported that the biological activities (promotion of adventitious root formation, inhibition of Avena straight growth and antifungal activity) of phyllosinol (epoxydon, 5) were partly reduced on the addition of cysteine.…”
mentioning
confidence: 99%